2010
DOI: 10.1186/1475-2859-9-100
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to folate overproduction in Lactobacillus plantarum WCFS1

Abstract: BackgroundUsing a functional genomics approach we addressed the impact of folate overproduction on metabolite formation and gene expression in Lactobacillus plantarum WCFS1. We focused specifically on the mechanism that reduces growth rates in folate-overproducing cells.ResultsMetabolite formation and gene expression were determined in a folate-overproducing- and wild-type strain. Differential metabolomics analysis of intracellular metabolite pools indicated that the pool sizes of 18 metabolites differed signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
(63 reference statements)
1
12
0
1
Order By: Relevance
“…Although it is useful during technological applications to increase folate production, a recent study has been shown that folate overproduction in Lact. plantarum WCFS1 significantly reduced the growth rate of this micro‐organism (Wegkamp et al. 2010).…”
Section: Folatesmentioning
confidence: 99%
“…Although it is useful during technological applications to increase folate production, a recent study has been shown that folate overproduction in Lact. plantarum WCFS1 significantly reduced the growth rate of this micro‐organism (Wegkamp et al. 2010).…”
Section: Folatesmentioning
confidence: 99%
“…Chemostat cultivation is highly valuable for this type of research, as it offers unique options for experimental design. In particular, chemostat cultivation enables researchers to manipulate individual cultivation parameters with minimal impact on other process conditions and at a fixed specific growth rate and, thereby, to dissect responses to individual environmental conditions (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…However, a recent comparative metabolomics and transcriptomics analysis of folate-overproducing Lactobacillus plantarum cells was reported to explain its reducing effect on the growth rate [99] . Remarkably, only little effect on the transcriptome and metabolome was observed but the great impact on the growth rate was explained by the gratuitous production of large amounts of folate-related transcripts and proteins.…”
Section: High Throughput Developments – Functional Analysis and Screementioning
confidence: 99%